Navigating couple and larger systems dynamics: Healthcare workers’ COVID‐19 experiences in Turkey - Arıcı‐Şahin, Fatma; Köse, Özlem (Wiley, 2025)
AbstractObjectiveThis study explored how caring for COVID‐19 patients impacted the marriages and support systems of healthcare workers in Turkey.BackgroundThe pandemic intensified mental health challenges for healthcare workers, significantly affecting their personal and professional relationships. Understanding the experiences of married healthcare workers is crucial for addressing unique stressors and enhancing relational resilience.MethodSeventeen healthcare professionals treating COVID‐19 patients were interviewed. Thematic analysis was used to examine couple dynamics and connections with broader support systems.ResultsWithin couple relationships, themes included communication patterns (both positive and negative), division of domestic labor, adherence to hygiene measures, emotional bonding and physical intimacy, and financial strains. At a broader systems level, participants described experiencing both supportive actions and emotional distance from their close social circles and organizational structures, underscoring the pandemic's complex influence on healthcare workers’ relational worlds.ConclusionMany participants reported strengthened relationships through shared activities and emotional support. However, some couples, burdened by long hours and lack of support, experienced negative interaction patterns.ImplicationsThe study highlights the influence of gender on the pandemic's impact on healthcare workers’ marriages and social connections, underscoring the need for targeted support systems during global health crises.